La comunicació des de la ciència: una assignatura encara pendent - Ramentol, Santiago (Tripodos. Facultat de Comunicació i Relacions Internacionals Blanquerna-URL, 2008)
In order to determine the areas in which scientific communication takes place and, in particular, communication from the field of science, this article establishes five circles. The first includes the interactions within each specialization; the second, the relations within the same branch of science; the third, within science as a whole; the fourth, within the society of knowledge, and the fifth, with society in general. From this starting point, diverse dysfunctions can be observed. In fact, communication works (though not without problems) in the framework of the relations between scientists in the same area of specialization. In this situation, two great channels of lateral communication are analyzed: journals and conferences. Outside of this first circle, many insufficienciesare detected in the descending communication (includingthe communication with other components of thesame branch of science). And communication with theman in the street is found to be minimal, disordered andoften incoherent.KEY WORDS: scientific communication; conferences;scientific journals; language; society of knowledge.PARAULES CLAU: comunicació científica; congressos;revistes científiques; llenguatge; societat del coneixement